Intra-household gender division of labour and decision-making on rice postharvest handling practices: A case of Eastern Uganda - Lusiba, Godfrey Ssebaggala (Cogent social sciences, 2017)
Gains in increasing productivity of grain in Sub-Saharan Africa are greatly undermined by the high postharvest losses (PHLs), which compromise the food and income security of households. Rice is one such important food and cash crop experiencing high PHLs. Given the limited mechanization of smallholder farms, PHLs result from practices influenced by knowledge, decision-making power in the household and cultural norms. Gender is an important consideration in the interaction of these factors especially for a duo purpose crop like rice serving both food and income security interests of households. A descriptive cross-sectional survey informed by qualitative focus group discussions was conducted in two major rice producing districts in Eastern Uganda to establish how gender division of labour and decision-making influence PHLs at the household level. The intra-household gender structure, division of labour and decision-making determine the postharvest loses of rice at the household level. Men and boys perform the labour intensive postharvest activities where postharvest losses are high. They also dominate decisions on the practices and technologies used. Due to labour intensity and cultural norms, households without men rely on hired labour, which increases their PHLs resulting from late access to and inadequate supervision of the hired labour. Interventions for reduction of PHLs at the household level must target men with better practices and simple cost-effective technologies.